Polymorphic stability of darunavir and its formulation - Corrêa, Josilene Chaves Ruela [UNESP]; Perissinato, Aline Gravinez; Dos Reis Serra, Cristina Helena; Trevisan, Marcello G.; Salgado, Hérida Regina Nunes [UNESP] (Springer Nature, 2016)
Darunavir (DAR) is a synthetic antiretroviral drug widely used around the world as an important component of HIV therapy. Usually, DAR is commercialized at ethanolate crystalline form. Under different environmental conditions, different pseudo-polymorphic forms arise and convert each other. The importance of the drug stability control is to ensure their quality, efficacy and safety. Therefore, the aim with this work was to evaluate the solid-state stability of DAR under stressed conditions and assess the role played by the formulation and package in providing stability to the drug. In this work, DAR ethanolate raw material and its tablet formulation were stocked under stress condition (55 °C) and monitored for 94 days. Thermal analysis (DSC and TG) and powder X-ray diffraction were used to evaluate possible polymorphic changes. There has been alteration of the crystalline structure of the raw material and the tablets stored outside of the primary packaging. However, the tablets kept within the primary package during the entire time remained with intact crystal structure, suggesting that as important as the formulation or coating is the protection provided by the packaging to the product used today. Thus, the packaging material to be used in the product containing DAR should be chosen carefully.
Keywords: Darunavir ethanolate; Drug formulation; Polymorphism; Stability